DRAFT POLICY GUIDE ON ETS (Tufts Archival Research Center, 2007)
Report on the Draft Policy Guide on Environmental Tobacco Smoke (ETS). Provides a detailed background on the Draft Policy Guide from 1988 to 1993. Includes notes from the June 23 1993 meeting of the Interagency Committee on Smoking and Health.